Multifunctionality of polymer composites : challenges and new solutions - Friedrich, Klaus, 1945-; Breuer, Ulf; ScienceDirect eBooks (Kidlington, Oxford : William Andrew is an imprint of Elsevier, 2015)
Multi-Functionality of Polymer Composites: Challenges and New Solutions brings together contributions from experts in the field of multifunctionality, presenting state-of-the-art discussion of this exciting and rapidly developing field, thus key enabling technologies for future applications. The text will enable engineers and materials scientists to achieve multifunctionality in their own products using different types of polymer matrices and various nano- and micro-sized fillers and reinforcements, including, but not limited to, carbon nanotubes and graphene. In addition, technologies for the integration of active materials such as shape memory alloys are discussed. The latest developments in a wide range of applications, including automotive/aerospace, electronics, construction, medical engineering, and future trends are discussed, making this book an essential reference for any researcher or engineer hoping to stay ahead of the curve in this high-potential area.
2.1.2 Multifunctional Composites2.1.3 Motivation and Outlines of This Chapter; 2.2 Innovative Multifunctional Carbon/Carbon Composites; 2.2.1 Introduction of Carbon/Carbon Composites; 2.2.2 Innovative Multifunctional Carbon/Carbon Composites via Nanotechnology; 2.2.2.1 Introduction; 2.2.2.2 Fabrication of composites; 2.2.2.3 Evaluation of heat-directed property; 2.2.3 Results and Discussion; 2.2.3.1 Determination of VGCF dispersion function; 2.2.3.2 Microscopic observations; 2.2.3.3 Experimental evaluation of heat-directed carbon/carbon composites
Online resource; title from PDF title page (Ebsco, viewed May 27, 2015).
"Plastics Design Library"--Cover
Includes bibliographical references and index.
Elsevier
Keywords: Polymeric composites; Composite materials; Polymers -- Additives; TECHNOLOGY & ENGINEERING / Engineering (General); TECHNOLOGY & ENGINEERING / Reference; Composite materials; Polymeric composites; Polymers -- Additives; Electronic books